(untitled) (Theatrum historiae, 2020)
In 1919 the International Midwives Union (IMU) was founded in Belgium. For two decades it was dominated by Professor Frans Daels from Belgium (1881-1974), a gynaecologist from Gent. Its main assembly was the bi-annual international congress, e.g. 1934 in London and 1936 in Berlin. In Berlin, the congress passed a resolution by which the chairing congress president would automatically become the IMU’s president for the following two years. Thus, Nanna Conti (1881-1951), the chairwoman of the German Midwives Association, became the first president of the IMU. After the congress in Paris in 1938 Clémence Mosse (d. 1949) became the next president. However, during the Second World War Mosse was unable to influence the IMU significantly. In 1942 Conti succeeded Daels as secretary general of the IMU and moved IMU headquarters to Berlin. At least from 1942-1945 the IMU was led by a Nazi functionary. This paper shows how the IMU reacted to the sometimes benevolent, sometimes dictatorial leadership of Nanna Conti and the spreading of Nazi propaganda among the European midwives. The situation between Czech and German midwives serves as a case example. The paper is based on the author’s biography of Nanna Conti.